GEOCHEMISTRY OF WATER-ROCK INTERACTION IN THE AREA OF THE KHIBINY ALKALINE MASSIF - Dudkin O.B.; Sandimirov S.S. (My University, 2007)
The interaction of natural and industrial waters with the rocks and apatite ores of the Khibiny alkaline massif was studied to estimate the extent of anthropogenic influence on natural processes. The abundance of the major rock-forming elements of the nepheline syenites and foidolites in the natural waters indicates that dissolution of nepheline and feldspathoids in natural water plays a significant role under the conditions of slow weathering in the Far North. Experiments showed that fine nepheline particles are transformed into amorphous phases at a fixed water volume at 18-20°C and pH 7.5-8.1. This process became observable already within the first day and continued for months. It is possible in stagnant reservoirs of natural waters and clearly expressed in industrial settling tanks. This is supported by the high content of amorphous phases enriched in Na, K, Al, and Si in the top layer of lacustrine sediments at the zone affected by the sewage of a concentrating mill. © Pleiades Publishing, Ltd. 2007.